KINERJA BANK PERKREDITAN RAKYAT (BPR) DALAM PENGUATAN UMKM - Lusy Lusy; Maria Widyastuti (Jurnal Akuntansi dan Pajak, 2023)
BPRs play an important role in strengthening the MSME economy. When the MSME sector has difficulty dealing with capital, they need the role of BPR for their business continuity. This study uses a qualitative descriptive approach by conducting observations and interviews with the BPR in Sidoarjo Regency and SMEs. The stages of research carried out include: (1) identifying the role of BPR; (2) conduct an in-depth analysis of the role of BPR in providing financial access to MSME actors; (3) conduct an analysis of BPR systems and procedures in providing financial access to MSME actors; (4) analyzing the service products offered by the BPR; and (5) reconstructing the various roles of BPRs to enhance the role of BPRs in improving the performance of MSMEs. The results of the study indicate that BPR plays a very important role in improving the performance of MSMEs. Even though it has played a role, in order to create business continuity, it is necessary to reconstruct the role of BPR in improving the performance of MSMEs, including: (1) Assistance to MSME actors related to innovation in the use of technology that can support the promotion of MSME products; (2) Assistance in the form of training related to strategies for creating different and distinctive products, in order to have a comparative advantage; (3) Assistance in the form of training related to customer service; and (4) capital building assistance in the form of management assistance and business supervision to customers.